Modeling of the Tensile Behavior FRCM Systems for Repair and Strengthening Interventions of Masonry Structures - Grande, Ernesto; Milani, Gabriele; Bertolesi, Elisa; Fagone, Mario; Rotunno, Tommaso (Frontiers in Built Environment, 2020)
Fiber Reinforced Cementitious Matrix (FRCM) systems have been recently introduced as an alternative solution for strengthening interventions of existing masonry and concrete constructions. The current literature provides interesting experimental and numerical studies which underline the potentialities of FRCMs together and their specific features. Direct tensile tests are generally used for characterizing the behavior of FRCM. Indeed, these tests underline the occurrence of important phenomena influencing the behavior of FRCM, such as the cracking of the matrix and the debonding of the reinforcement from the matrix. The present paper aims at numerically analyzing the response of FRCM systems during tensile tests carried out throughout different setup configurations. To this end, a simple model carried out from literature and opportunely modified is presented in the paper and validated with reference to experimental case studies. Moreover, the obtained results are critically analyzed in order to emphasize the role of the proposed model for the interpretation of the results carried out from standard tensile tests.